BUILDING AI SUCCESS: THE DEFINITIVE PROGRAM MANAGEMENT FRAMEWORK - Anusha Akkiraju (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
In this article, we have devised an outline pertaining to the primary elements of AI program management with regards to its implementation in a variety of organizations. The outline is comprised of components such as the strategy, human resource management, technology, risk, ethics, and finance. It gladly observes that with proper analysis on the global implementations and industry practices, the increase in project success, operational efficiency, and stakeholder satisfaction contributes significantly. This approach provides real solutions to the most problematic aspects of AI adoption, as well as offering actionable advice for program managers so they can deal without much hassle with the intricacies of AI. In this regard, the article speaks on the importance of utilizing multidisciplinary leadership, cross-functional quality assurance, and ethical AI measures and compliance in order to aid organizations optimize their AI use while ensuring maximized ROI.